สารผลิตภัณฑ์ธรรมชาติกลุ่มฟีนอลิกที่มีฤทธิ์ยับยั้งการสร้างเม็ดสี - อิสรีย์ จรรยารติพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Nowadays, the world is facing global warming. Sunlight can stimulate more melanin pigment that causes dull skin, wrinkles, freckles, melasma and skin cancer. This research focused on melanogenesis inhibitory activity of the extracts from Limnophila aromatica (Lam.) Merr., a local plant found in all regions of Thailand and the major constituents are phenolic. Two pure compounds, 5-demethyl tangeretin and xanthomicrol were purified from L. aromatica (Lam.) Merr. The structures of the isolated compounds were confirmed by spectroscopic methods, mainly NMR and IR spectroscopy. In addition, fifty subfractions were obtained and were tested for their anti-melanogenesis by Mushroom tyrosinase inhibition assay on TLC and 96-well plates, used L-tyrosine and L-DOPA as a substrate and Kojic acid as a positive control to obtain their IC₅₀. The results showed subfraction D4.5 provided the most potent activity with IC₅₀ values of 9.66 and 11.25 μg/mL for L-tyrosine and L-DOPA, respectively. Moreover, subfraction D4.5 did not show any significant cytotoxicity at concentrations of 50 and 100 μg/mL. Therefore, it can be further purified for use as a medicine or cosmetic that is effective in inhibiting melanin pigments.